Pengembangan Sistem Penjualan Koperasi POM AU Lanud Iswahjudi Magetan - Kasfia Jihan Dzahabiyyah Hasna'; Denny Sagita Rusdianto; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
PRIMKOPAU "WIRA WASKITA" SATPOM or the POM AU cooperative Iswahjudi Air Force is a primary cooperative that has a waserda shop or unit. In sales activities, members can make payments in two ways, namely cash and debt. Every time there is a sales transaction, the seller will make records. In recording this, sellers often forget or enter incorrect notes because it is still done manually. In addition, the cooperative also provides credit for goods in collaboration with other stores. Each month, the shop department sends an invoice to the payer, which will be deducted from the member's salary. In searching and calculating these bills, it took the store department a long time to produce a list of these bills. With a system in the form of a website that can record sales, be able to calculate installments automatically, generate a list of bills, good stock management of goods, can help and prevent cooperatives from losing. In carrying out its development, it resulted in 17 functional requirements and 1 non-functional requirement. System testing is carried out using white-box testing for unit testing, black-box testing for functional testing and compatibility testing to find out whether the system can run on various hardware and various software.